VD_FINDINFO HC / 2022 / 345 vom 1. April 2022 - VD Tribunal cantonal (2022)
JONCTION DE CAUSES, DÉCISION DE RENVOI, MAXIME INQUISITOIRE, MAXIME DE DISPOSITION | 132 CPC (CH), 247 al. 2 CPC (CH), 56 CPC (CH), 58 al. 1 CPC (CH)